Performance indicators in speed climbing: insights from the literature supplemented by a video analysis and expert interviews - Askari Hosseini, S.; Wolf, P. (Frontiers in Physiology, 2023)
Due to the goal of mastering a standardised route with relatively large handholds as quickly as possible, the weighting of performance-determining factors might be different in speed climbing in comparison to lead climbing or bouldering. The objective of this paper was to identify physical and tactical factors for peak performance in speed climbing. Therefore, not only existing literature was reviewed but also a video analysis of the final round of speed climbing at the Olympic games and interviews with experts were done. Out of two hundred and one articles initially found by searching in Medline, Elsevier and Google Scholar databases, 38 were ultimately considered. Generally, an increased lower limb power, a small body mass index, an improved anaerobic glycogen system, and a high fluency in movements were identified as characteristics for high-speed climbing performance. Based on video analysis of Olympic games, coordinated motions, correct foot movements and shorter reaction time could take a novice speed climber to an elite level. Furthermore, male climbers should avoid pairing hands on holds. Considering the increasing popularity, the continued improvement of the record time in this discipline, and the currently limited amount of relevant literature should stimulate future studies on performance-determining variables, assessments, and training methods to maintain the attractiveness of speed climbing.